Unveiling vocabulary teaching and learning beliefs of teachers and learners in an EFL context - Hassan A. Alshumrani (Asian-Pacific Journal of Second and Foreign Language Education, 2024)
Abstract Vocabulary is often considered as a key predictor of second language ability, and how teachers and learners’ beliefs and conceptualizations about vocabulary affect their teaching and learning has recently gained unprecedented momentum in the field of second language education. However, despite their importance, there is a paucity of research that has combined data from teachers and learners to illuminate their beliefs and conceptualizations. The main aim of this quantitative study is to combine data from English language teachers and learners to explore their beliefs and conceptualizations about vocabulary learning and knowledge. The study voluntarily recruited 113 learners and 91 teachers from a major Saudi university to fill out an online questionnaire. The findings revealed that both teachers and learners generally valued vocabulary on a par with grammar, listening, speaking, reading, and writing, and that both groups showed a general understanding of the basic components of word knowledge; however, their beliefs differed significantly. The results also indicated that despite showing an awareness of the role of textbooks and the incidental approach to vocabulary learning, there were significant differences in teachers and learners’ beliefs. The study concluded with a range of suggested implications, as well as suggestions for further studies on how to address the present lacunae in the field.